Pengembangan Media Pembelajaran Kearsipan Aplikasi Powtoon Pada Kelas X SMK Negeri 2 Padang - Lifia Wahyuni; Armida S (Jurnal Salingka Nagari, 2023)
Learning media is not only a supporter in achieving learning objectives but as a communication tool that is able to increase student motivation and foster creativity in learning, for that it needs to be developed according to the needs of students. PowToon application learning media development for archival subjects was developed by taking into account the feasibility of indicators in terms of material, media language and evaluation. This study is a Research and Development study using the Dick and Carey model, this research was piloted at SMK N 2 Padang in class X OTKP students by taking into account the feasibility of expert validators, namely materials, media, language and evaluations from lecturers and teachers who are competent in their fields. The results of this study can be conveyed that the development of learning media for the PowToon application for archival subjects, the material indicators develop are feasible to use because they have reached a 98% practicality test level. In terms of presenting the feasibility of the evaluation presented, it is feasible even though it must pay attention to the stimulus, object and subject objectives by formulating indicators operationally